Avoiding burnout (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. According to an Indeed survey in 2021, more than half of employees suffered from burnout. Officially recognised as an occupational phenomenon in 2019 by the World Health Organization, burnout is characterised by symptoms including emotional exhaustion, cynicism, and inefficacy. It has been linked to mental and physical health problems, including but not limited to increased risk of coronary artery disease, depression and anxiety. In this track, we provide a better understanding of burnout, and we offer multiple, actionable techniques to help alleviate burnout. Learning Objectives Learn what burnout is, and what's behind it Learn actionable techniques to limit the negative effects of, and even prevent burnout.